Design of Controlling and Monitoring System for Room Temperature, Lighting, Power, and Energy Using Internet of Things - Ida Bagus Irawan Purnama; I Kadek Endra Sutawan; I Gede Agus Antara Putra; I Putu Agastia Kama Suika; I Gede Ketut Sri Budarsa; I Made Purbhawa (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2022)
One goal of a smart home is to save the use of energy. Savings can be made with a control system where the things related to electricity usage will be controlled automatically. This research designs a control system of several parameters in a replica of a room with a monitoring application. Those parameters include room temperature, lighting, voltage, current, power, and energy using the Internet of Things. The room temperature control system uses the DHT11 sensor, the light intensity controller uses the LDR HL01 sensor module, while measuring current, voltage, power, and electrical energy at the load uses the PZEM-004T sensor. The NodeMCU ESP8266 is used as a control center that receives, processes, and sends data to the Blynk application using WiFi. The core of the system is based on the detection of the room temperature threshold and the state of light intensity based on light or dark. From these two conditions, the control center will instruct the relay to turn on or turn off the fan and lighting according to the predefined conditions. If the load is on then the voltage, current, power, and energy data will be acquired and displayed on the Blynk application in real-time.